Regulating Twisted Skeleton to Construct Organ‐Specific Perylene for Intensive Cancer Chemotherapy - Liu, Zhonghua; Wang, Xuejuan; Chen, Qing; Ma, Feiyan; Huang, Yongwei; Gao, Yijian; Deng, Qingyuan; Qiao, Zeng‐Ying; Xing, Xiaoyi; Zhu, Jianling; Lu, Feng; Wang, Hao (Angewandte Chemie International Edition, 2021)
The systemic use of pharmaceutical drugs for cancer patients is a compromise between desirable therapy and side effects because of the intrinsic shortage of organ‐specific pharmaceutical drug. Design and construction of pharmaceutical drug to achieve the organ‐specific delivery is thus desperately desirable. We herein regulate perylene skeleton to effect organ‐specificity and present an example of lung‐specific distribution on the basis of bay‐twisted PDIC‐NC. We further demonstrate that PDIC‐NC can target into mitochondria to act as cellular respiration inhibitor, inducing insufficient production of adenosine triphosphate, promoting endogenous H2O2 and .OH burst, elevating calcium overload, efficiently triggering the synergistic apoptosis, autophagy and endoplasmic reticulum stress of lung cancer cells. The antitumor performance of PDIC‐NC is verified on in vivo xenografted, metastasis and orthotopic lung cancer, presenting overwhelming evidences for potentially clinical application. This study contributes a proof‐of‐concept demonstration of twisted perylene to well attain lung‐specific distribution, and meanwhile achieves intensive lung cancer chemotherapy. Herein we modulate the perylene skeleton to effect organ‐specificity and present an example of lung‐specific distribution on the basis of a twisted perylene PDIC‐NC. The in vitro and in vivo biological functions of PDIC‐NC are demonstrated and its molecular mechanism for the inhibiting activity on tumour cells is revealed.